SERS and DFT study of copper surfaces coated with corrosion inhibitor - Muniz-Miranda, Maurizio; Muniz-Miranda, Francesco; Caporali, Stefano (Beilstein Journal of Nanotechnology, 2014)
Azole derivatives are common inhibitors of copper corrosion due to the chemical adsorption occurring on the metal surface that gives rise to a protective film. In particular, 1,2,4-triazole performs comparable to benzotriazole, which is much more widely used, but is by no means an environmentally friendly agent. In this study, we have analyzed the adsorption of 1,2,4-triazole on copper by taking advantage of the surface-enhanced Raman scattering (SERS) effect, which highlights the vibrational features of organic ligand monolayers adhering to rough surfaces of some metals such as gold, silver and copper. To ensure the necessary SERS activation, a roughening procedure was implemented on the copper substrates, resulting in nanoscale surface structures, as evidenced by microscopic investigation. To obtain sufficient information on the molecule–metal interaction and the formation of an anticorrosive thin film, the SERS spectra were interpreted with the aid of theoretical calculations based on the density functional theory (DFT) approach.
Keywords: copper corrosion; DFT; inhibitor film; 1,2,4-triazole; SERS

(untitled) - Fox, P. G.; Bradley, P. A. (Corros. Sci., 1980)

(untitled) - Sherif, E.-S. M.; Erasmus, R. M.; Comins, J. D. (J. Colloid Interface Sci., 2007)

(untitled) - Sherif, E.-S. M.; Erasmus, R. M.; Comins, J. D. (J. Colloid Interface Sci., 2007)

(untitled) - Sherif, E.-S. M.; Erasmus, R. M.; Comins, J. D. (J. Colloid Interface Sci., 2007)

(untitled) - Khiati, Z.; Othman, A. A.; Sanchez-Moreno, M.; Bernard, M.-C.; Joiret, S.; Sutter, E. M. M.; Vivier, V. (Corros. Sci., 2011)

(untitled) - John, S.; Joseph, A. (Mater. Chem. Phys., 2012)

(untitled) - Jiang, L.; Lan, Y.; He, Y.; Li, Y.; Li, Y.; Luo, J. (Thin Solid Films, 2014)

Surface Enhanced Raman Spectroscopy: Analytical, Biophysical and Life Science Applications - Schlücker, S. (Wiley-VCH, 2011)

(untitled) - Muniz-Miranda, M. (J. Raman Spectrosc., 1996)

(untitled) - Muniz-Miranda, M.; Puggelli, M.; Ricceri, R.; Gabrielli, G. (Langmuir, 1996)

(untitled) - Pergolese, B.; Muniz-Miranda, M.; Bigotto, A. (J. Phys. Chem. B, 2006)

(untitled) - Lesar, A.; Milošev, I. (Chem. Phys. Lett., 2009)

(untitled) - Muniz-Miranda, M.; Pergolese, B.; Bigotto, A. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Pagliai, M.; Caporali, S.; Muniz-Miranda, M.; Pratesi, G.; Schettino, V. (J. Phys. Chem. Lett., 2012)

(untitled) - Muniz-Miranda, M.; Pergolese, B.; Muniz-Miranda, F.; Caporali, S. (J. Alloys Compd., 2014)

Principles of Surface-Enhanced Raman Spectroscopy and Related Plasmonic Effects - Le Ru, E. C.; Etchegoin, P. G. (Elsevier, 2009)

(untitled) - Shin, K. S.; Lee, H. S.; Joo, S. W.; Kim, K. (J. Phys. Chem. C, 2007)

(untitled) - Cox, J. R.; Woodcock, S.; Hillier, I. H.; Vincent, M. A. (J. Phys. Chem., 1990)

(untitled) - Davarski, K. A.; Khalachev, N. K.; Yankova, R. Z.; Raikov, S. (Chem. Heterocycl. Compd., 1998)

(untitled) - Balabin, R. M. (J. Chem. Phys., 2009)

(untitled) - Jiménez, V.; Alderete, J. B. (J. Mol. Struct.: THEOCHEM, 2006)

(untitled) - Bolton, K.; Brown, R. D.; Burden, F. R.; Mishra, A. (J. Mol. Struct., 1975)

(untitled) - Chiang, J. F.; Lu, K. C. (J. Mol. Struct., 1977)

(untitled) - Billes, F.; Endrédi, H.; Keresztury, G. (J. Mol. Struct.: THEOCHEM, 2000)

(untitled) - Gutowski, K. E.; Rogers, R. D.; Dixon, D. A. (J. Phys. Chem. A, 2006)

(untitled) - Chan, H. Y. H.; Takoudis, C. G.; Weaver, M. J. (J. Phys. Chem. B, 1999)

(untitled) - Niaura, G. (Electrochim. Acta, 2000)

(untitled) - Brandão, C. R. R.; Costa, L. A. F.; Breyer, H. S.; Rubim, J. C. (Electrochem. Commun., 2009)

Gaussian 09, Revision C.01 (Gaussian, Inc., 2010)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Vosko, S. H.; Wilk, L.; Nusair, M. (Can. J. Phys., 1980)

(untitled) - Stephens, P. J.; Devlin, F. J.; Chabalowski, C. F.; Frisch, M. J. (J. Phys. Chem., 1994)

(untitled) - Muniz-Miranda, M.; Pagliai, M.; Muniz-Miranda, F.; Schettino, V. (Chem. Commun., 2011)

(untitled) - Pagliai, M.; Muniz-Miranda, F.; Schettino, V.; Muniz-Miranda, M. (Progr. Colloid Polym. Sci., 2012)

(untitled) - Muniz-Miranda, M.; Pagliai, M. (J. Phys. Chem. C, 2013)